2006
DOI: 10.1097/01.tp.0000214934.48677.e2
|View full text |Cite
|
Sign up to set email alerts
|

Organization of a High-Volume Kidney Transplant Program???The ???Assembly Line??? Approach

Abstract: This report describes the organization of a high-volume Brazilian kidney transplant program. With use of an "assembly line" approach, 2,461 kidney transplantations were performed between 1999 and 2004, fulfilling government expectations without compromising the care of the patients. The annual number of kidney transplants increased from 428 to 656 per year. In our Organ Procurement Organization (with 7 million inhabitants), brain death notifications increased from 196 to 461, but less than 25% became actual do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
24
0
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(31 citation statements)
references
References 31 publications
2
24
0
5
Order By: Relevance
“…[1][2][3] Their results are equally impressive with 5-year graft survival of 93.1% for living and 79.7% for decreased donors, figures that at least rival or even surpass graft survival rates in the United States according to the 2015 Scientific Registry of Transplant Recipients (SRTR). 1,4 One interesting area of comparison is the incidence of acute rejection, which approaches 25% of transplant recipients at Hospital do Rim, compared to approximately 8% in the United States between 2013-2014.…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…[1][2][3] Their results are equally impressive with 5-year graft survival of 93.1% for living and 79.7% for decreased donors, figures that at least rival or even surpass graft survival rates in the United States according to the 2015 Scientific Registry of Transplant Recipients (SRTR). 1,4 One interesting area of comparison is the incidence of acute rejection, which approaches 25% of transplant recipients at Hospital do Rim, compared to approximately 8% in the United States between 2013-2014.…”
mentioning
confidence: 89%
“…1,2 Their reported outcomes and progress is astonishing with the single hospital having performed 11,436 kidney transplants over an 18-year period.…”
mentioning
confidence: 99%
“…Previous studies showed that the number of kidney transplant increased significantly after establishment of the central coordinating organizations. (19) …”
Section: Organ Procurement and Allocationmentioning
confidence: 99%
“…The waiting times for kidney transplant surgery are from 3 to 6 years, and even longer in several countries such as United Kingdoms, Brazil, and Taiwan. (17)(18)(19)(20) Therefore, many countries encourage expanded criteria donor (ECD) and donor after cardiac death (DCD). These two polices can increase amount of transplant surgery and reach good transplant results under well-planned and cooperative organizations.…”
Section: Kidney Transplant and Donor Shortagementioning
confidence: 99%
“…10 Our sample, primarily young adults, white, and receiving a kidney from a living donor, is representative of most kidney transplant patients in Brazil. 20 The Brazilian organ donation system has become more efficient in recent years, and the number of deceased-donor kidney transplants has surpassed that of living-donor kidney transplants in 2008. 10,18 In our region, kidneys from deceased donors were available only after 2009, explaining the small percentage of kidney transplants from deceased donors in the studied sample.…”
Section: Discussionmentioning
confidence: 99%